Public Health Education: An Agenda for Communicable Disease Control in Africa - Ememabasi , Bassey; Ikorok , Maria Michael (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The purpose of this paper was to examine the role of public health education and in the control of communicable diseases in Africa and highlights the responsibilities of the Health Educator. It was shown that communicable diseases account for a significant proportion of the global disease burden and are a major cause of death and disability on sub-Saharan Africa. Core role of health education as a communicable disease prevention strategy were highlighted to include: preparedness, commitment, containment and case management, surveillance, and evaluation community participation for communicable disease control. Prevention of communicable diseases was considered in the work as the best form of control by the application of simple low cost, and cost effective preventive and intervention strategies. Public health education was viewed in the work as a core intervention in the prevention and control of communicable. It was recommended that public health education professionals should facilitated to exercise their role for health promotion in the multi-disciplinary and collaborative health team the world over